Microbial Study of Pathogenic Bacterial that Producing Biofilm Isolated From Fresh Red Meat - Ali Abd Kadhum; Hanaa khaleel Ibraheim (مجلة الانبار للعلوم البيطرية)
Contamination of meats with different species of microorganisms pose significant threats not only to the human health but also to the animal production. This study was conducted to investigate the presence of bacterial contaminants in raw meat of livestock. A total of 75 random samples were collected (included 50 cow samples and 25 goats samples) from several butcher shops and slaughterhouse stores in Basrah governorate. The samples were subjected into the biochemical tests using Enter system 18R to confirm preliminary bacterial diagnosis and subsequently cultured using a selective media (MacConkey agar). The outcomes demonstrated Escherichia. coli was the dominate bacterial isolated species in the cow and goats with the percentage estimated at (30%) and (28%), respectively. Other important isolations were also found Enterobacter cloacae in was a rate (20%) Cow meat and Klebsiella pneumonia in goat meat with a rate estimated at (20%), while the lowest isolations rate was Salmonella spp (8%) in cow meat. Staphylococcus aureus (14%) in cow meat and (12%) in goat meat. In conclusion, meats are representative the source of infection with foodborne pathogens carry hazard to public health transmitted to the humans due to mishandling and improper hygienic condition of meats. The results showed biofilm production were high percent for Staphylococcus aureus 5 (50%) strong biofilm producer, follow Klebsiella pneumonia 4 (30.76%) strong biofilm. As other isolates were biofilm producer and production of biofilm is related to the resistance.